Analysis Of Differences in Stress Levels of Nurses Working in Isolation and Non-Isolation Wards for Covid-19 In General Hospital Royal Prima Medan - Stefenie; Ermi Girsang; Linda Chiuman; Sri Wahyuni Nasution (CV. Inara, 2022)
Along with the escalating number of confirmed cases of COVID-19, it becomes a big demand for medical staff, in particular nurses, as the frontline in caring COVID-19 patients, this makes nurses’ stress levels to build up. So, this research aims to describe the factors that affect stress levels experienced by nurses during the pandemic COVID-19. The purpose of this study is to analyze the differences in stress levels of nurses working in isolation and non isolation wards for COVID 19 in General Hospital Royal Prima Medan. Type of research used in this research is quantitative research by using Cross Sectional approach. The results obtained from this research is that the majority of nurses in non isolation ward have stress levels that are still within normal limits with good performance and moderate workload, and the majority of nurses in isolation ward have a high level of stress with poor performance and a heavy workload. Workload (OR =5.21 95%CI 2.47-10.95; p=0.015), Performance (OR =2.60 95%CI 1.38-4.91; p=0.002), and Work Unit (OR =5.33 95%CI 2.65-10.75; p=0.029) significantly affect the sress level of nurses working at General Hospital Royal Prima Medan.